Physiological and therapeutic differences between vitamin D, its metabolites and analogues - Kanis, J; Russell, G; Smith, R (1977)
Since several metabolites and analogues of vitamin D have become available, their physiological and therapeutic potential have been studied in various disorders of mineral metabolism, particularly those classically termed vitamin D resistant. In some instances this resistance appears to be due to defective metabolism of vitamin D or to defective target organ responses, but in others it is not. Although the precise effect of vitamin D or its metabolites on mineralization of bone is still unknown there is some evidence that the metabolites differ in their relative effects on intestine, bone, muscle and parathyroid glands. These differences may eventually have therapeutic values. At present the major advantage of 1α-hydroxylated derivatives of vitamin D over other compounds resides in their more rapid onset and reversal of action which makes them much easier and safer to use.